2021
DOI: 10.1002/jgh3.12370
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of anti‐tumor necrosis factor therapy and surgery in nonperianal fistulizing Crohn's disease

Abstract: Background Unlike perianal fistula, long‐term outcomes of nonperianal fistulae (NPF) in Crohn's disease (CD) are not clear. We aimed to compare the outcomes of medical and surgical therapies in patients with NPF. Methods We retrospectively analyzed the records of patients of CD with NPF who were prospectively followed from January 2005 to December 2018. Results Of the 53 patients with NPF [mean age at presentation:29 ± 14 years; 54.7% male; median duration of follow‐up: 47 months (interquartile range [IQR]:26–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Nevertheless, no The American Journal of GASTROENTEROLOGY randomized placebo-controlled trial has directly evaluated the efficacy of biologic agents when stricturing or penetrating disease has already developed (6). In addition, surgical management should be also discussed with these patients, including aspects such as the risk of postoperative recurrence, the need for prophylactic therapy, and even further surgical interventions (18). Previous studies evaluating different types of fistulas and outcomes showed that anti-TNF agents may be effective in this setting (6,18), although this has been mostly in small case series and only in the short term (8,(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, no The American Journal of GASTROENTEROLOGY randomized placebo-controlled trial has directly evaluated the efficacy of biologic agents when stricturing or penetrating disease has already developed (6). In addition, surgical management should be also discussed with these patients, including aspects such as the risk of postoperative recurrence, the need for prophylactic therapy, and even further surgical interventions (18). Previous studies evaluating different types of fistulas and outcomes showed that anti-TNF agents may be effective in this setting (6,18), although this has been mostly in small case series and only in the short term (8,(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, surgical management should be also discussed with these patients, including aspects such as the risk of postoperative recurrence, the need for prophylactic therapy, and even further surgical interventions (18). Previous studies evaluating different types of fistulas and outcomes showed that anti-TNF agents may be effective in this setting (6,18), although this has been mostly in small case series and only in the short term (8,(19)(20)(21)(22)(23). In a cohort of 93 patients with penetrating disease (77% entero-enteric or entero-colonic, 17% entero-vesical, and 5% entero-vaginal), 27% of patients achieved fistula closure after 5 years of follow-up, and 47% required surgery (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding CD sub-phenotypes, patients with inflammatory phenotype (B1) respond better to infliximab [12], while patients with stricturing disease (B2) correlate with long term lack of response [142]. In patients with penetrating CD (B3), the response to anti-TNF depends on the type of fistulae; in patients with perianal fistulae both adalimumab and infliximab seem effective [23], with therapeutic drug monitoring levels being indicative of the response [143][144][145][146], while in patients with non-perianal fistulae, surgery seems to be unavoidable [147].…”
Section: Clinical Factors That Influence Biologic Therapy's Successmentioning
confidence: 99%